Raiva em herbívoros no rio grande do norte: um diagnóstico situacional - Feitoza Neto, Francisco Fernandes (Universidade Federal Rural do Semi-Árido, 2019)
Rabies is considered one of the most important animal and public health zoonoses, not only for its drastic and fatal evolution, but also for its high economic and social cost. It is characterized as a progressive viral encephalitis that affects mammals and has a wide geographical distribution. The rabies virus belongs to the family Rhabdoviridae and genus Lyssavirus, presenting antigenic variants, according to their respective natural hosts. Herbivores are accidental hosts of the rabies virus, and the bovine species has been reported as the most affected by the disease, being linked to the presence of hematophagous bats in rural areas. Given the importance of the disease to the human and animal population, the serious economic damage that can occur to livestock, as well as the scarcity of epidemiological studies on herbivores in the state of Rio Grande do Norte, the objective of this study was to conduct a survey of the epidemiological situation of rabies in Herbivores in the state of Rio Grande do Norte. The information was collected from the database of the Central Laboratory of Public Health (LACEN) and the State Department of Public Health (SESAP) of Rio Grande do Norte, from 2006 to 2018 and the following variables were evaluated: species involved , number of cases per year, monthly distribution, spatial distribution and viral typification. Quantitative analyzes were performed using software: Microsoft Excel 2007® and MapInfo 10.0, presented in tables, graphs and maps, emphasizing the pertinent information to absolute and relative values. The results showed that herbivorous rabies was present in Rio Grande do Norte in a total of 105 cases, the majority (89) occurred in cattle representing 84.8% of the cases, followed by horses (13), sheep (02) and donkey (01). The largest number of cases occurred in 2014 and 2015 and in May and October. The spatial distribution revealed that 40 municipalities reported cases in all four regions of the state and the western region was the one that concentrated the largest number of positive municipalities (14). As for viral typing, only the variant V3 was found in the state. The findings presented here are of concern as it confirms the circulation and wide viral distribution of rabies in domestic herbivores in Rio Grande do Norte and may pose risks to the human population and bring serious economic damage to livestock, highlighting a challenge for health authorities, requiring integrated and effective control and prevention measures
Monografia
Keywords: Defesa Sanitária; Epidemiologia; Lyssavirus; Epidemiology; Health Defense; Lyssavirus; CIENCIAS AGRARIAS::MEDICINA VETERINARIA